O impacto emocional do 11 de setembro entre os imigrantes mexicanos de Chicago (Estados Unidos) - doi:10.5020/18061230.2006.p175 - Francisco Sacristán Romero (Universidade de Fortaleza, 2012)
"Nerve illness" is an ancient biomedical disease taxon, which notion has been re-elaborated in folk contexts. Today it is considered a taxon illness in many western (or westernized) societies expressing a way of suffering. This study explores the impact of the 11-S on the nerves of Mexican migrants living in the United States. The perspective taken for the analysis was guided by the tradition of the Anthropology of illness. The paper is supported on original materials, gathered in Highland Park (Illinois, USA). The fieldwork was conducted from September 2001 to February 2002 among users of the "Latino Program" of the Agency "Family Service of South lake County". The data were collected trough depth interviews to qualified informants. Three main dimensions were considered. First, the impact of the Towers episode on the Mexican migrants' daily life, the way their health were affected, and how illness of nerves was originated and manifested. Second was taken into account some particularly treats, like the uncertainty about their future and their fear, not only linked to the possibilities of new attacks but also related to the internal changes and Federal policies. Third, was explored how Mexican identity was redefined as a result of the attack. In the immediate moments actors expressed feelings of being part of the risk, sharing with the Anglo-Americans a condensed and common history. However, later on this feeling turned into the opposite emotion, when they experienced the increasing hostility against minorities. This situation triggered, even more than the attack itself, the suffering of nerves.